Method for recycling waste graphite lithium-ion battery negative electrode plate

Through thermal decomposition and ammonia absorption treatment combined with iron salt solution precipitation, the problems of low recovery rate and waste of resources in the lithium-ion battery recycling process are solved, and efficient recycling and high-value conversion of lithium, phosphorus, fluorine and sulfur elements are achieved.

CN119495862BActive Publication Date: 2025-04-29CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510083636.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

Smart Images

  • Figure CN119495862B_ABST
    Figure CN119495862B_ABST
Patent Text Reader

Abstract

The present application relates to a method for recycling waste graphite-based lithium-ion battery negative electrode sheets, comprising: thermally decomposing the negative electrode sheets to be recycled; subjecting the tail gas obtained by the thermal decomposition treatment to ammonia water absorption treatment to obtain an absorption liquid; adjusting the pH value of the absorption liquid to 8.0-10, using an iron salt solution to precipitate the absorption liquid, and collecting a first precipitate and a first reaction liquid; performing resin weight removal on the first reaction liquid to obtain a lithium precipitation liquid; performing sulfuric acid leaching and solid-liquid separation on the solid material obtained by the thermal decomposition treatment in sequence, and recovering graphite and a first filtrate; adjusting the pH value of the first filtrate to 4.0-4.5, and collecting lithium fluoride and a second filtrate; performing precipitation treatment on the second filtrate, and collecting a second precipitate and a second reaction liquid; performing resin weight removal and concentration treatment on the second reaction liquid to obtain a mixed solution containing ammonium fluoride and ammonium sulfate; mixing the mixed solution with the lithium precipitation liquid to obtain a lithium fluoride and ammonium sulfate solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for recycling waste graphite-based lithium-ion battery negative electrode plates. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the rapid expansion of the lithium-ion battery market, more and more waste lithium-ion batteries are facing recycling problems.

[0004] The negative electrode obtained after the detailed disassembly of waste lithium-ion batteries contains a large amount of lithium, which has a very high recycling value. At present, the traditional recycling process mostly uses pure acid leaching and then pure alkali precipitation to recover lithium, which has a low recovery rate and produces a large amount of low value-added product sodium sulfate, while phosphorus and fluorine elements mostly form solid waste products calcium phosphate and calcium fluoride, resulting in a huge waste of resources. Summary of the invention

[0005] The present application provides a method for recycling waste graphite-based lithium-ion battery negative electrode plates to effectively recover lithium, phosphorus, fluorine and sulfur.

[0006] In order to achieve the above object, the present application provides a method for recycling waste graphite-based lithium-ion battery negative electrode sheets, comprising the following steps:

[0007] Thermal decomposition treatment of the negative electrode sheets to be recycled;

[0008] The tail gas obtained by the thermal decomposition treatment is subjected to ammonia water absorption treatment to obtain an absorption liquid;

[0009] The pH value of the absorption liquid is adjusted to 8.0-10, and the absorption liquid is precipitated with an iron salt solution to collect a first precipitate and a first reaction liquid;

[0010] Performing resin deweighting on the first reaction solution to obtain a lithium precipitation solution;

[0011] The solid material obtained by thermal decomposition treatment is sequentially subjected to sulfuric acid leaching and solid-liquid separation to recover graphite and a first filtrate;

[0012] Adjusting the pH value of the first filtrate to 4.0-4.5, collecting lithium fluoride and the second filtrate;

[0013] Performing precipitation treatment on the second filtrate, collecting a second precipitate and a second reaction liquid;

[0014] The second reaction solution is subjected to resin deweighting and concentration treatment to obtain a mixed solution containing ammonium fluoride and ammonium sulfate;

[0015] The mixed solution is mixed with the lithium precipitation solution to obtain a lithium fluoride and ammonium sulfate solution.

[0016] Therefore, the present application introduces materials such as iron salt solution, ammonia solution and sulfuric acid solution to recover phosphorus element to obtain iron phosphate that can be used to prepare lithium iron phosphate, recover fluorine element to obtain lithium fluoride that can be used to produce lithium hexafluorophosphate, and recover sulfur element to obtain ammonium sulfate, thereby converting phosphorus element, fluorine element and sulfur element into high-value products, avoiding the generation of large amounts of solid waste products such as calcium phosphate, calcium sulfate, calcium fluoride and low value-added sodium sulfate products.

[0017] In some embodiments, the ammonia absorption treatment includes at least one of the following conditions:

[0018] (1) using an ammonia solution with a mass percentage concentration of 25wt%-30wt% to carry out the ammonia absorption treatment;

[0019] (2) The ammonia absorption treatment is performed using an ammonia solution with a mass percentage concentration of 25wt%-30wt%, and the mass ratio of the ammonia solution to the negative electrode plate is (60-100):1000.

[0020] In some embodiments, the precipitation treatment of the absorption liquid with an iron salt solution comprises at least one of the following conditions:

[0021] (1) The iron salt solution includes one or more of a saturated iron sulfate solution and a saturated iron fluoride solution;

[0022] (2) The iron salt solution includes one or more of a saturated iron sulfate solution and a saturated iron fluoride solution, and the mass ratio of the iron salt solution to the negative electrode plate is (30-50):1000.

[0023] In some embodiments, before the step of using an iron salt solution to precipitate the absorption liquid, the method further includes: purifying the absorption liquid after pH adjustment.

[0024] In some embodiments, an ammonia solution with a mass percentage concentration of 25wt%-30wt% is used to adjust the pH value of the absorption liquid to 8.0-10.

[0025] In some embodiments, after the tail gas is subjected to ammonia absorption treatment, the step of subjecting the tail gas to sulfuric acid treatment and sodium hydroxide treatment is also included.

[0026] In some embodiments, the pH value of the first sulfuric acid solution used for the sulfuric acid treatment is 1-3.

[0027] In some embodiments, the pH value of the sodium hydroxide solution used for the sodium hydroxide treatment is 10-13.

[0028] In some embodiments, the mass percentage concentration of the second sulfuric acid solution used for the sulfuric acid leaching is 3wt%-10wt%, and the solid-liquid mass ratio during sulfuric acid leaching is 1:(1-40).

[0029] In some embodiments, the pH value of the first filtrate is adjusted to 4.0-4.5 using an ammonia solution with a mass percentage concentration of 25wt%-30wt%.

[0030] In some embodiments, the step of subjecting the second filtrate to precipitation treatment comprises:

[0031] The second filtrate is mixed with a saturated solution of iron sulfate.

[0032] In some embodiments, the thermal decomposition treatment comprises calcination, the calcination temperature is 250° C.-550° C., the calcination time is 0.5 h-3 h, and the calcination atmosphere comprises nitrogen.

[0033] In some embodiments, the first precipitate and the second precipitate each independently comprise iron phosphate.

[0034] In some embodiments, the concentration process comprises an RO membrane concentration process.

[0035] In some embodiments, the method further comprises the step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate.

[0036] In some embodiments, the step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate comprises:

[0037] The ammonium sulfate solution is sequentially subjected to lithium extraction resin treatment, calcium method defluorination, calcium removal treatment, pH adjustment and evaporation crystallization to obtain the pure ammonium sulfate.

[0038] In some embodiments, the resin used in the lithium extraction resin treatment is a cation exchange resin.

[0039] In some embodiments, calcium oxide is used for the calcium-based defluorination, and the amount of calcium oxide used is to adjust the pH value of the ammonium sulfate solution to a pH value ≥ 12.

[0040] In some embodiments, the decalcification treatment is performed using carbon dioxide.

[0041] In some embodiments, after the decalcification treatment and the pH adjustment, the pH value of the ammonium sulfate solution is 10-11.

[0042] In some embodiments, the evaporative crystallization comprises:

[0043] After the pH-adjusted ammonium sulfate solution is subjected to solid-liquid separation, the solution obtained after solid-liquid separation is evaporated and crystallized using an MVR crystallization system. Details of one or more embodiments of the present application are presented in the following drawings and descriptions. Other features, objects, and advantages of the present application will become apparent from the specification, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0045] Figure 1 This is a flow chart of a negative electrode plate recycling process according to one embodiment of the present application. DETAILED DESCRIPTION

[0046] Below, some embodiments of the method for recycling waste graphite-based lithium-ion battery negative electrode sheets of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0047] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0048] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0049] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0051] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0052] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0053] Lithium-ion batteries using graphite as the negative electrode active material are prone to the phenomenon that lithium is not removed in time and deposited on the negative electrode sheet during the charging and discharging process. In addition, after abuse under high and low temperatures, overcharge and overdischarge or other special working conditions, the deposition of lithium on the negative electrode sheet is also very serious. Through disassembly, it can be found that there is a large amount of metallic lithium on the surface of the negative electrode sheet, and it is rapidly oxidized in the air. If the lithium deposited on the negative electrode sheet cannot be reasonably recovered, it will not only waste lithium resources, but also pollute the environment. At present, traditional recovery processes mostly use pure acid leaching and then pure alkali precipitation lithium recovery, with a low recovery rate and a large amount of low value-added product sodium sulfate, while phosphorus and fluorine elements mostly form solid waste products calcium phosphate and calcium fluoride, causing great waste of resources. Therefore, this application introduces materials such as iron salt solution, ammonia solution and sulfuric acid solution when recycling the negative electrode sheet to convert phosphorus, fluorine and sulfur into high-value products, avoiding the production of a large amount of solid waste products such as calcium phosphate, calcium sulfate, calcium fluoride and low value-added sodium sulfate products.

[0054] One or more embodiments of the present application provide a method for recycling waste graphite-based lithium-ion battery negative electrode sheets, comprising the following steps:

[0055] The negative electrode plates to be recovered are subjected to thermal decomposition treatment; the tail gas obtained by the thermal decomposition treatment is subjected to ammonia water absorption treatment to obtain an absorption liquid; the pH value of the absorption liquid is adjusted to 8.0-10, the absorption liquid is subjected to precipitation treatment with an iron salt solution, and a first precipitate and a first reaction liquid are collected; the first reaction liquid is subjected to resin deweighting to obtain a lithium precipitation liquid; the solid material obtained by the thermal decomposition treatment is subjected to sulfuric acid leaching and solid-liquid separation in sequence, and graphite and a first filtrate are recovered; the pH value of the first filtrate is adjusted to 4.0-4.5, and lithium fluoride and a second filtrate are collected; the second filtrate is subjected to precipitation treatment, and a second precipitate and a second reaction liquid are collected; the second reaction liquid is subjected to resin deweighting and concentration treatment to obtain a mixed solution containing ammonium fluoride and ammonium sulfate; the mixed solution is mixed with the lithium precipitation liquid to obtain a lithium fluoride and ammonium sulfate solution.

[0056] It should be noted that the negative electrode sheet mentioned in the context is the negative electrode sheet obtained after detailed disassembly of the lithium-ion battery.

[0057] During the thermal decomposition treatment, the lithium hexafluorophosphate contained in the negative electrode sheet is decomposed into lithium fluoride and phosphorus pentafluoride. The reaction process is: .

[0058] The chemical reactions that occur during ammonia absorption treatment are as follows:

[0059] .

[0060] The first reaction liquid contains ammonium fluoride and ammonium sulfate.

[0061] After the thermal decomposition treatment, tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil are obtained. The mixture containing graphite and copper foil is firstly sieved to separate the copper foil, and after obtaining a solid material containing graphite, the solid material is acid leached.

[0062] The "resin weight removal" mentioned above and below refers to the removal of heavy metals using resins.

[0063] In some embodiments, the tail gas is subjected to a two-stage ammonia absorption treatment, during which the ammonia absorbs byproducts such as HF and phosphorus pentafluoride in the tail gas.

[0064] As a non-limiting example, the pH value of the absorption liquid can be adjusted to pH 8.0, 8.5, 9, 9.5, 10 or a range between any two of the above values, etc., without specific limitation. When the pH value of the absorption liquid is adjusted within the above range, it is beneficial to improve the exhaust gas purification effect, while improving the utilization rate of raw materials and reducing waste.

[0065] As a non-limiting example, the pH of the first filtrate can be adjusted to pH 4.0, 4.1, 4.2, 4.3, 4.4, 4.5 or a range between any two of the above values, etc., without specific limitation.

[0066] Understandably, the method for recycling waste graphite-based lithium-ion battery negative electrode sheets provided in the present application, by introducing materials such as iron salt solution, ammonia solution and sulfuric acid solution, recovers phosphorus element to obtain iron phosphate that can be used to prepare lithium iron phosphate, recovers fluorine element to obtain lithium fluoride that can be used to produce lithium hexafluorophosphate, and recovers sulfur element to obtain ammonium sulfate, thereby converting phosphorus element, fluorine element and sulfur element into high-value products, avoiding the generation of a large amount of solid waste products such as calcium phosphate, calcium sulfate, calcium fluoride and low value-added sodium sulfate products. In some embodiments, the first precipitate and the second precipitate each independently include iron phosphate.

[0067] In some embodiments, an ammonia solution having a mass percentage concentration of 25 wt %-30 wt % is used for ammonia absorption treatment; for example, the mass percentage concentration of the ammonia solution can be but is not limited to 25 wt %, 26 wt %, 27 wt %, 28 wt %, 29 wt %, 30 wt % or a range between any two of the above concentrations, etc.

[0068] As a possible implementation mode, when the ammonia water absorption treatment is carried out, the mass ratio of the ammonia solution with a mass percentage concentration of 25wt%-30wt% and the negative electrode plate is (60-100):1000; for example, it can be but not limited to 60:1000, 65:1000, 70:1000, 75:1000, 80:1000, 85:1000, 90:1000, 95:1000, 100:1000 or the range between any two of the above mass ratios.

[0069] As a possible implementation, the iron salt solution includes one or more of a saturated iron sulfate solution and a saturated iron fluoride solution.

[0070] In some exemplary embodiments, the mass ratio of the iron salt solution to the negative electrode plate is (30-50):1000; for example, it can be but not limited to 30:1000, 35:1000, 40:1000, 45:1000, 50:1000 or a range between any two of the above ratios.

[0071] In some exemplary embodiments, an ammonia solution with a mass percentage concentration of 25wt%-30wt% is used to adjust the pH value of the absorption liquid to 8.0-10. The concentration of the ammonia solution used to adjust the pH value of the absorption liquid can be, but is not limited to, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt% or a range between any two of the above concentrations.

[0072] In some embodiments, before the step of using the iron salt solution to precipitate the absorption liquid, the step further includes: purifying the absorption liquid after the pH is adjusted.

[0073] As a possible implementation method, after the tail gas is subjected to ammonia water absorption treatment, the method further includes the steps of subjecting the tail gas to sulfuric acid treatment and sodium hydroxide treatment.

[0074] In some optional embodiments, during the sulfuric acid treatment, a pH meter is used to inject the first sulfuric acid solution.

[0075] As a possible implementation, the pH value of the first sulfuric acid solution used for sulfuric acid treatment is 1-3; for example, it can be but not limited to 1, 1.5, 2, 2.5, 3 or a range between any two of the above pH values.

[0076] It should be noted that, in the context, "first sulfuric acid solution", "second sulfuric acid solution", "first filtrate", "second filtrate", "first reaction solution", "second reaction solution", "first precipitate", "second precipitate", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0077] In some embodiments, when the sodium hydroxide treatment is performed, a pH meter is used to inject sodium hydroxide solution.

[0078] As a possible implementation manner, the pH value of the sodium hydroxide solution used for the sodium hydroxide treatment is 10-13; for example, it can be but not limited to 10, 10.5, 11, 11.5, 12, 12.5, 13 or a range between any two of the above pH values.

[0079] In some embodiments, the mass percentage concentration of the second sulfuric acid solution used for sulfuric acid leaching is 3wt%-10wt%; for example, it can be but not limited to 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt% or the range between any two of the above values.

[0080] As a possible implementation mode, the solid-liquid mass ratio during sulfuric acid leaching is 1:(1-40), that is, the mass ratio of the solid material to the second sulfuric acid solution is 1:(1-40); for example, it can be but not limited to 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:26, 1:28, 1:30, 1:32, 1:34, 1:36, 1:38, 1:40 or the range between any two of the above mass ratios.

[0081] In some embodiments, the pH value of the first filtrate is adjusted to 4.0-4.5 using an ammonia solution having a mass percentage concentration of 25wt%-30wt%. As an example, the mass percentage concentration of the ammonia solution used to adjust the pH value of the first filtrate can be, but is not limited to, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt% or a range between any two of the above mass concentrations.

[0082] In some embodiments, the step of subjecting the second filtrate to precipitation treatment includes: mixing the second filtrate with a saturated iron sulfate solution.

[0083] It should be noted that when the second filtrate is mixed with the saturated ferric sulfate solution, since the saturated ferric sulfate solution is weakly acidic, it may be necessary to use an ammonia solution to adjust the pH of the system to a pH of 4.0-4.5, and the corresponding product contains ferric hydroxide.

[0084] In some embodiments, the thermal decomposition treatment comprises calcination.

[0085] In some exemplary embodiments, the calcination temperature is 250°C-550°C; for example, it may be but is not limited to 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range between any two of the above temperatures.

[0086] In some embodiments, the calcination time is 0.5 h-3 h; for example, it can be but not limited to 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h or a range between any two of the above times.

[0087] In some alternative embodiments, the calcination atmosphere comprises nitrogen.

[0088] It should be noted that the calcination temperature and time can be combined in any appropriate manner, and both can be selected from any calcination temperature and time described herein. In some embodiments, the concentration treatment includes RO membrane concentration treatment.

[0089] In some embodiments, the method further comprises the step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate.

[0090] In some embodiments, the step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate includes: sequentially subjecting the ammonium sulfate solution to lithium extraction resin treatment, calcium method defluorination, calcium removal treatment, pH adjustment and evaporation crystallization to obtain pure ammonium sulfate.

[0091] In some alternative embodiments, dilute sulfuric acid is used for pH adjustment.

[0092] As a non-limiting example, the resin used in the lithium extraction resin treatment is a cation exchange resin.

[0093] It should be noted that after the lithium-extracting resin treatment, the resin can be subjected to lithium-removal treatment to obtain a lithium-removal liquid, and the lithium-removal liquid is used in the process of acid leaching of solid materials containing graphite.

[0094] In some embodiments, calcium oxide is used for calcium-based defluorination, and the amount of calcium oxide used is to adjust the pH value of the ammonium sulfate solution to ≥12.

[0095] As a possible implementation, carbon dioxide is used for the decalcification treatment.

[0096] In some exemplary embodiments, after the decalcification treatment, the pH value of the ammonium sulfate solution is 10-11 after pH adjustment.

[0097] As a possible implementation, the evaporative crystallization includes: performing solid-liquid separation on the pH-adjusted ammonium sulfate solution, and then performing evaporative crystallization on the solution obtained after the solid-liquid separation using an MVR crystallization system.

[0098] like Figure 1 As shown, as a non-limiting example, the process flow for recycling waste graphite-based lithium-ion battery negative electrode sheets includes the following steps:

[0099] Step S1, mechanically crushing the negative electrode plates obtained by finely disassembling the lithium-ion battery, and then conveying them to a rotary kiln for calcination, so as to thermally decompose the electrolyte and lithium hexafluorophosphate contained in the negative electrode plates to obtain tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil.

[0100] Step S2, conveying the tail gas containing organic gas and phosphorus pentafluoride into the tail gas combustion chamber, and using the heat of the tail gas to heat the rotary kiln; after the combusted tail gas is cooled and dust-purified, it enters the two-stage ammonia tail gas absorption tower for ammonia absorption treatment, and uses ammonia to fully absorb by-products such as hydrogen fluoride and phosphorus pentafluoride in the tail gas, and then passes through the three-stage acid washing tower and the four-stage alkali washing tower for acid absorption and alkali absorption to obtain an absorption liquid, and the tail gas is discharged after meeting the national standard.

[0101] Step S3, after adjusting the pH value of the absorption liquid obtained by the ammonia absorption treatment to 8-10 with an ammonia solution, filtering and purifying the absorption liquid, and then adding an iron salt solution to the absorption liquid for precipitation treatment, after solid-liquid separation, iron phosphate and a first reaction liquid containing ammonium fluoride and ammonium sulfate are obtained, and the first reaction liquid is subjected to resin deweighting and used as a lithium precipitation liquid for standby use.

[0102] Step S4, after screening the mixture containing graphite and copper foil obtained by the thermal decomposition treatment in step S1 to separate the copper foil, the solid material containing graphite is subjected to sulfuric acid leaching and solid-liquid separation in sequence to recover the graphite and the first filtrate; the pH value of the first filtrate obtained by solid-liquid separation is adjusted to pH 4.0-4.5 with an ammonia solution, and then filtered to separate the precipitated small amount of lithium fluoride to obtain LiF and a second filtrate.

[0103] Step S5, adding ferric sulfate solution to the second filtrate for precipitation treatment to obtain ferric phosphate and a second reaction solution, performing resin deweighting on the second reaction solution, and then concentrating it through an RO membrane to obtain a mixed solution containing ammonium fluoride and ammonium sulfate.

[0104] Step S6: Mix the lithium precipitation solution obtained in step S3 with a mixed solution containing ammonium fluoride and ammonium sulfate to obtain a lithium fluoride and ammonium sulfate solution.

[0105] Step S7, treating the ammonium sulfate solution with a lithium extraction resin to extract residual lithium elements to obtain an ammonium sulfate solution after complete lithium extraction.

[0106] Step S8, adding calcium oxide to the ammonium sulfate solution after complete lithium extraction to perform calcium method defluorination, and after the pH value reaches a pH value ≥ 12, performing solid-liquid separation to obtain the ammonium sulfate solution after defluorination.

[0107] Step S9, after quantitatively introducing carbon dioxide into the ammonium sulfate solution after defluorination for decalcification treatment, the pH value thereof is adjusted to 10-11 and then solid-liquid separation is performed to obtain a pure sulfuric acid solution, and the pure ammonium sulfate solution is transported to the MVR crystallization system for evaporation and crystallization to obtain an ammonium sulfate product.

[0108] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0109] Example 1

[0110] Step S1, taking 1000g of the disassembled and recovered negative electrode plates, mechanically crushing them, and then transporting them to a tubular furnace for calcination to thermally decompose the electrolyte and lithium hexafluorophosphate contained in the negative electrode plates to obtain tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil; wherein the calcination temperature is 300°C and the time is 2h.

[0111] Step S2, conveying the tail gas containing organic gas and phosphorus pentafluoride into the tail gas combustion chamber, and using the heat of the tail gas to heat the rotary kiln; after the combusted tail gas is cooled and dusted, it enters the two-stage ammonia tail gas absorption tower for ammonia absorption treatment, and uses ammonia to fully absorb by-products such as hydrogen fluoride and phosphorus pentafluoride in the tail gas, and then passes through the three-stage acid washing tower and the four-stage alkali washing tower for acid absorption and alkali absorption. The tail gas is discharged after meeting the national standard; wherein the mass percentage concentration of the ammonia solution is 30wt%, and the dosage is 100g (100kg / ton).

[0112] Step S3, after adjusting the pH value of the absorption liquid obtained by the ammonia absorption treatment with an ammonia solution to 8.3, the absorption liquid is filtered and purified, and then 170g of a saturated solution of ferric sulfate is added to the absorption liquid for precipitation treatment, and after solid-liquid separation, 19.2g of ferric phosphate and a first reaction liquid containing ammonium fluoride and ammonium sulfate are obtained. After the first reaction liquid is deweighted by resin, it is used as a lithium precipitation liquid for standby use.

[0113] Step S4, after screening the mixture containing graphite and copper foil obtained by the thermal decomposition treatment in step S1 to separate the copper foil, the solid material containing graphite is subjected to sulfuric acid leaching and solid-liquid separation in sequence, and the graphite and the first filtrate are recovered, wherein 5L of a dilute sulfuric acid solution with a mass percentage concentration of 5wt% is used for sulfuric acid leaching, and the leaching solid-liquid mass ratio is 1:5; 155mL of an ammonia solution with a mass percentage concentration of 30wt% is used to adjust the pH value of the first filtrate obtained by solid-liquid separation to 4.2, and the precipitated small portion of lithium fluoride is separated to obtain LiF and a second filtrate.

[0114] Step S5, adding 10 mL of saturated ferric sulfate solution to the second filtrate for precipitation treatment, filtering to obtain ferric phosphate and a second reaction liquid, deweighting the second reaction liquid with a resin, and then concentrating it through an RO membrane to obtain a concentrated mixed solution containing ammonium fluoride and ammonium sulfate.

[0115] Step S6: Mix the lithium precipitate solution obtained in step S3 with a mixed solution containing ammonium fluoride and ammonium sulfate, and separate the solid and liquid to obtain 26.7 g of lithium fluoride and ammonium sulfate solution.

[0116] Step S7, subjecting the ammonium sulfate solution to lithium extraction resin treatment to extract residual lithium elements and obtain an ammonium sulfate solution after complete lithium extraction; wherein the resin used in the lithium extraction resin treatment is a cation exchange resin, Dusheng CH-90 resin.

[0117] Step S8, adding 20.5 g of calcium oxide to the ammonium sulfate solution after complete lithium extraction to perform calcium method defluorination, and after the pH value reaches a pH value ≥ 12, performing solid-liquid separation to obtain the ammonium sulfate solution after defluorination.

[0118] Step S9, after quantitatively introducing carbon dioxide into the ammonium sulfate solution after defluorination for decalcification treatment, the pH value thereof is adjusted to 10.3 and then solid-liquid separation is performed to obtain a pure sulfuric acid solution, and the pure ammonium sulfate solution is transported to the MVR crystallization system for evaporation and crystallization to obtain 353.2 g of ammonium sulfate product; wherein the carbon dioxide flow rate is 1 L / M, and the carbon dioxide introduction time is 5.6 minutes.

[0119] Example 2

[0120] Step S1, taking 1000g of the disassembled and recovered negative electrode plates, mechanically crushing them, and then transporting them to a tubular furnace for calcination to thermally decompose the electrolyte and lithium hexafluorophosphate contained in the negative electrode plates to obtain tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil; wherein the calcination temperature is 350°C and the time is 2h.

[0121] Step S2, conveying the tail gas containing organic gas and phosphorus pentafluoride into the tail gas combustion chamber, and using the heat of the tail gas to heat the rotary kiln; after the combusted tail gas is cooled and dusted, it enters the two-stage ammonia tail gas absorption tower for ammonia absorption treatment, and uses ammonia to fully absorb by-products such as hydrogen fluoride and phosphorus pentafluoride in the tail gas, and then passes through the three-stage acid washing tower and the four-stage alkali washing tower for acid absorption and alkali absorption. The tail gas is discharged after meeting the national standard; wherein the mass percentage concentration of the ammonia solution is 30wt%, and the dosage is 100g (100kg / ton).

[0122] Step S3, after adjusting the pH value of the absorption liquid obtained by the ammonia absorption treatment to 8.5 with an ammonia solution, the absorption liquid is filtered and purified, and then 170g of a saturated solution of ferric sulfate is added to the absorption liquid for precipitation treatment, and after solid-liquid separation, 19.8g of ferric phosphate and a first reaction liquid containing ammonium fluoride and ammonium sulfate are obtained. After the first reaction liquid is deweighted by resin, it is used as a lithium precipitation liquid for standby use.

[0123] Step S4, after screening the mixture containing graphite and copper foil obtained by the thermal decomposition treatment in step S1 to separate the copper foil, the solid material containing graphite is subjected to sulfuric acid leaching and solid-liquid separation in sequence, and the graphite and the first filtrate are recovered, wherein 5L of a dilute sulfuric acid solution with a mass percentage concentration of 5wt% is used for sulfuric acid leaching, and the leaching solid-liquid mass ratio is 1:5; 158mL of an ammonia solution with a mass percentage concentration of 30wt% is used to adjust the pH value of the first filtrate obtained by solid-liquid separation to 4.3, and then filtered to separate the precipitated small amount of lithium fluoride to obtain LiF and a second filtrate.

[0124] Step S5, adding 10 mL of saturated ferric sulfate solution to the second filtrate for precipitation treatment, filtering to obtain ferric phosphate and a second reaction liquid, deweighting the second reaction liquid with a resin, and then concentrating it through an RO membrane to obtain a concentrated mixed solution containing ammonium fluoride and ammonium sulfate.

[0125] Step S6: Mix the lithium precipitate solution obtained in step S3 with a mixed solution containing ammonium fluoride and ammonium sulfate, and separate the solid and liquid to obtain 27.5 g of lithium fluoride and ammonium sulfate solution.

[0126] Step S7, subjecting the ammonium sulfate solution to lithium extraction resin treatment to extract residual lithium elements and obtain an ammonium sulfate solution after complete lithium extraction; wherein the resin used in the lithium extraction resin treatment is a cation exchange resin, Dusheng CH-90 resin.

[0127] Step S8, adding 20.8 g of calcium oxide to the ammonium sulfate solution after complete lithium extraction to perform calcium method defluorination, and after the pH value reaches a pH value ≥ 12, performing solid-liquid separation to obtain the ammonium sulfate solution after defluorination.

[0128] Step S9, after quantitatively introducing carbon dioxide into the ammonium sulfate solution after defluorination for decalcification treatment, the pH value thereof is adjusted to 10.4 and then solid-liquid separation is performed to obtain a pure sulfuric acid solution, and the pure ammonium sulfate solution is transported to the MVR crystallization system for evaporation and crystallization to obtain 347.7 g of ammonium sulfate product; wherein the carbon dioxide flow rate is 1 L / M, and the carbon dioxide introduction time is 6.3 minutes.

[0129] Example 3

[0130] Step S1, taking 1000g of the disassembled and recovered negative electrode plates, mechanically crushing them, and then transporting them to a tubular furnace for calcination to thermally decompose the electrolyte and lithium hexafluorophosphate contained in the negative electrode plates to obtain tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil; wherein the calcination temperature is 500°C and the time is 2h.

[0131] Step S2, conveying the tail gas containing organic gas and phosphorus pentafluoride into the tail gas combustion chamber, and using the heat of the tail gas to heat the rotary kiln; after the combusted tail gas is cooled and dusted, it enters the two-stage ammonia tail gas absorption tower for ammonia absorption treatment, and uses ammonia to fully absorb by-products such as hydrogen fluoride and phosphorus pentafluoride in the tail gas, and then passes through the three-stage acid washing tower and the four-stage alkali washing tower for acid absorption and alkali absorption. The tail gas is discharged after meeting the national standard; wherein the mass percentage concentration of the ammonia solution is 30wt%, and the dosage is 100g (100kg / ton).

[0132] Step S3, after adjusting the pH value of the absorption liquid obtained by the ammonia absorption treatment to 8.8 with an ammonia solution, the absorption liquid is filtered and purified, and then 170g of a saturated solution of ferric sulfate is added to the absorption liquid for precipitation treatment, and after solid-liquid separation, 20.4g of ferric phosphate and a first reaction liquid containing ammonium fluoride and ammonium sulfate are obtained. After the first reaction liquid is deweighted by resin, it is used as a lithium precipitation liquid for standby use.

[0133] Step S4, after screening the mixture containing graphite and copper foil obtained by the thermal decomposition treatment in step S1 to separate the copper foil, the solid material containing graphite is subjected to sulfuric acid leaching and solid-liquid separation in sequence, and the graphite and the first filtrate are recovered, wherein 5L of a dilute sulfuric acid solution with a mass percentage concentration of 5wt% is used for sulfuric acid leaching, and the leaching solid-liquid mass ratio is 1:5; 145mL of an ammonia solution with a mass percentage concentration of 30wt% is used to adjust the pH value of the first filtrate obtained by solid-liquid separation to 4.4, and the precipitated small portion of lithium fluoride is separated to obtain LiF and a second filtrate.

[0134] Step S5, adding 10 mL of saturated ferric sulfate solution to the second filtrate for precipitation treatment, filtering to obtain ferric phosphate and a second reaction liquid, deweighting the second reaction liquid with a resin, and then concentrating it through an RO membrane to obtain a concentrated mixed solution containing ammonium fluoride and ammonium sulfate.

[0135] Step S6: Mix the lithium precipitate solution obtained in step S3 with a mixed solution containing ammonium fluoride and ammonium sulfate, and separate the solid and liquid to obtain 28.5 g of lithium fluoride and ammonium sulfate solution.

[0136] Step S7, subjecting the ammonium sulfate solution to lithium extraction resin treatment to extract residual lithium elements and obtain an ammonium sulfate solution after complete lithium extraction; wherein the resin used in the lithium extraction resin treatment is a cation exchange resin, Dusheng CH-90 resin.

[0137] Step S8, adding 22g of calcium oxide to the ammonium sulfate solution after complete lithium extraction to perform calcium method defluorination, and after the pH value reaches a pH value ≥ 12, performing solid-liquid separation to obtain the ammonium sulfate solution after defluorination.

[0138] Step S9, after quantitatively introducing carbon dioxide into the ammonium sulfate solution after defluorination for decalcification treatment, the pH value thereof is adjusted to 10.5 and then solid-liquid separation is performed to obtain a pure sulfuric acid solution, and the pure ammonium sulfate solution is transported to the MVR crystallization system for evaporation and crystallization to obtain 356.2 g of ammonium sulfate product; wherein the carbon dioxide flow rate is 1 L / M, and the carbon dioxide introduction time is 7.5 minutes.

[0139] Example 4

[0140] In step S3 of Example 4, a saturated ferric fluoride solution is used instead of a saturated ferric sulfate solution. The specific recovery method of Example 4 is as follows:

[0141] Step S1, taking 1000g of the disassembled and recovered negative electrode plates, mechanically crushing them, and then transporting them to a tubular furnace for calcination to thermally decompose the electrolyte and lithium hexafluorophosphate contained in the negative electrode plates to obtain tail gas containing organic gas and phosphorus pentafluoride and a mixture containing graphite and copper foil; wherein the calcination temperature is 500°C and the time is 2h.

[0142] Step S2, conveying the tail gas containing organic gas and phosphorus pentafluoride into the tail gas combustion chamber, and using the heat of the tail gas to heat the rotary kiln; after the combusted tail gas is cooled and dusted, it enters the two-stage ammonia tail gas absorption tower for ammonia absorption treatment, and uses ammonia to fully absorb by-products such as hydrogen fluoride and phosphorus pentafluoride in the tail gas, and then passes through the three-stage acid washing tower and the four-stage alkali washing tower for acid absorption and alkali absorption. The tail gas is discharged after meeting the national standard; wherein the mass percentage concentration of the ammonia solution is 30wt%, and the dosage is 100g (100kg / ton).

[0143] Step S3, after adjusting the pH value of the absorption liquid obtained by the ammonia absorption treatment to 8.9 with an ammonia solution, the absorption liquid is filtered and purified, and then 97g of a saturated solution of iron fluoride is added to the absorption liquid for precipitation treatment, and 20.4g of iron phosphate and a first reaction liquid containing ammonium fluoride are obtained after solid-liquid separation. After the first reaction liquid is deweighted by resin, it is used as a lithium precipitation liquid for standby use.

[0144] Step S4, after screening the mixture containing graphite and copper foil obtained by the thermal decomposition treatment in step S1 to separate the copper foil, the solid material containing graphite is subjected to sulfuric acid leaching and solid-liquid separation in sequence, and the graphite and the first filtrate are recovered, wherein 5L of a dilute sulfuric acid solution with a mass percentage concentration of 5wt% is used for sulfuric acid leaching, and the leaching solid-liquid mass ratio is 1:5; 145mL of an ammonia solution with a mass percentage concentration of 30wt% is used to adjust the pH value of the first filtrate obtained by solid-liquid separation to 4.4, and the precipitated small portion of lithium fluoride is separated to obtain LiF and a second filtrate.

[0145] Step S5, adding 10 mL of saturated ferric sulfate solution to the second filtrate for precipitation treatment, filtering to obtain ferric phosphate and a second reaction liquid, deweighting the second reaction liquid with a resin, and then concentrating it through an RO membrane to obtain a concentrated mixed solution containing ammonium fluoride and ammonium sulfate.

[0146] Step S6: Mix the lithium precipitate solution obtained in step S3 with a mixed solution containing ammonium fluoride and ammonium sulfate, and separate the solid and liquid to obtain 28.5 g of lithium fluoride and ammonium sulfate solution.

[0147] Step S7, subjecting the ammonium sulfate solution to lithium extraction resin treatment to extract residual lithium elements and obtain an ammonium sulfate solution after complete lithium extraction; wherein the resin used in the lithium extraction resin treatment is a cation exchange resin, Dusheng CH-90 resin.

[0148] Step S8, adding 22g of calcium oxide to the ammonium sulfate solution after complete lithium extraction to perform calcium method defluorination, and after the pH value reaches a pH value ≥ 12, performing solid-liquid separation to obtain the ammonium sulfate solution after defluorination.

[0149] Step S9, after quantitatively introducing carbon dioxide into the ammonium sulfate solution after defluorination for decalcification treatment, the pH value thereof is adjusted to 10.5 and then solid-liquid separation is performed to obtain a pure sulfuric acid solution, and the pure ammonium sulfate solution is transported to the MVR crystallization system for evaporation and crystallization to obtain 328g of ammonium sulfate product; wherein the carbon dioxide flow rate is 1L / M, and the carbon dioxide introduction time is 7.5 minutes.

[0150] Comparative Example 1

[0151] In the recovery process of Comparative Example 1, the tail gas was not subjected to ammonia water absorption treatment, resulting in that HF ​​and PF5 in the tail gas could not be fully absorbed, thereby causing the tail gas emission to fail to meet the requirements.

[0152] Comparative Example 2

[0153] In the recovery process of Comparative Example 2, a saturated solution of ferric sulfate was not used. Since the concentration of the ferric sulfate solution was too low, the concentrations of the reaction solution and the lithium precipitation solution were too low, and the expected recovery rate could not be achieved, and even LiF could not be obtained.

[0154] The above embodiments and comparative examples were subjected to iron phosphate detection, lithium fluoride detection and ammonium sulfate detection, and the detection methods and requirements were as follows:

[0155] Iron phosphate testing standards and requirements: refer to HG∕T 4701-2014, iron phosphate for batteries.

[0156] Lithium fluoride testing standards and requirements: refer to GB / T 22666-2008.

[0157] Ammonium sulfate testing standards and requirements: refer to GB / T 535-2020.

[0158] The test results of iron phosphate are shown in Table 1.

[0159] Table 1

[0160]

[0161] The detection results of lithium fluoride are shown in Table 2.

[0162] Table 2

[0163]

[0164] The test results of ammonium sulfate are shown in Table 3.

[0165] Table 3

[0166]

[0167] As shown in Tables 1 to 3, the method for recycling the negative electrode sheet of waste graphite-based lithium-ion batteries provided by the present application is used to recover phosphorus to obtain iron phosphate, recover fluorine to obtain lithium fluoride, and recover sulfur to obtain ammonium sulfate by introducing materials such as iron salt solution, ammonia solution, and sulfur solution. The obtained iron phosphate, lithium fluoride, and ammonium sulfate have high purity, few impurities, and high utilization value. Thus, phosphorus, fluorine, and sulfur are converted into high-value products through the recycling process, avoiding the generation of a large amount of solid waste products and low-value-added sodium sulfate products.

[0168] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.

[0169] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for recycling waste graphite lithium-ion battery negative electrode plates, characterized in that: The steps include: Thermal decomposition treatment of the negative electrode sheets to be recycled; The tail gas obtained by the thermal decomposition treatment is subjected to ammonia water absorption treatment to obtain an absorption liquid; The pH value of the absorption liquid is adjusted to 8.0-10 by using an ammonia solution with a mass percentage concentration of 25wt%-30wt%, and the absorption liquid is precipitated by using an iron salt solution to collect a first precipitate and a first reaction liquid; the iron salt solution includes one or more of a saturated iron sulfate solution and a saturated iron fluoride solution; Performing resin deweighting on the first reaction solution to obtain a lithium precipitation solution; The solid material obtained by thermal decomposition treatment is sequentially subjected to sulfuric acid leaching and solid-liquid separation to recover graphite and a first filtrate; The pH value of the first filtrate is adjusted to 4.0-4.5 using an ammonia solution with a mass percentage concentration of 25wt%-30wt%, and lithium fluoride and a second filtrate are collected; mixing the second filtrate with a saturated iron sulfate solution to perform a precipitation treatment on the second filtrate, and collecting a second precipitate and a second reaction solution; The second reaction solution is subjected to resin deweighting and concentration treatment to obtain a mixed solution containing ammonium fluoride and ammonium sulfate; The mixed solution is mixed with the lithium precipitation solution to obtain a lithium fluoride and ammonium sulfate solution.

2. The method according to claim 1, characterized in that The ammonia absorption treatment includes at least one of the following conditions: (1) using an ammonia solution with a mass percentage concentration of 25wt%-30wt% to carry out the ammonia absorption treatment; (2) The ammonia absorption treatment is performed using an ammonia solution with a mass percentage concentration of 25wt%-30wt%, and the mass ratio of the ammonia solution to the negative electrode plate is (60-100):1000.

3. The method according to claim 1, characterized in that The mass ratio of the iron salt solution to the negative electrode plate is (30-50):1000.

4. The method according to claim 1, characterized in that After the tail gas is subjected to ammonia water absorption treatment, the method further includes the steps of subjecting the tail gas to sulfuric acid treatment and sodium hydroxide treatment.

5. The method according to claim 4, characterized in that The pH value of the first sulfuric acid solution used for the sulfuric acid treatment is 1-3.

6. The method according to claim 4, characterized in that The pH value of the sodium hydroxide solution used for the sodium hydroxide treatment is 10-13.

7. The method according to claim 1, characterized in that The mass percentage concentration of the second sulfuric acid solution used for the sulfuric acid leaching is 3wt%-10wt%, and the solid-liquid mass ratio during the sulfuric acid leaching is 1:(1-40).

8. The method according to claim 1, characterized in that The thermal decomposition treatment comprises calcination, the calcination temperature is 250° C.-550° C., the calcination time is 0.5 h-3 h, and the calcination atmosphere comprises nitrogen.

9. The method according to claim 1, characterized in that The first precipitate and the second precipitate each independently include iron phosphate.

10. The method according to claim 1, characterized in that The concentration process includes RO membrane concentration process.

11. The method according to any one of claims 1 to 10, characterized in that The method also includes the step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate.

12. The method according to claim 11, characterized in that The step of purifying the ammonium sulfate solution to obtain pure ammonium sulfate comprises: The ammonium sulfate solution is sequentially subjected to lithium extraction resin treatment, calcium method defluorination, calcium removal treatment, pH adjustment and evaporation crystallization to obtain the pure ammonium sulfate.

13. The method according to claim 12, characterized in that The resin used in the lithium extraction resin treatment is a cation exchange resin.

14. The method according to any one of claims 12 to 13, characterized in that: Calcium oxide is used for the calcium method defluorination, and the amount of calcium oxide used is to adjust the pH value of the ammonium sulfate solution to ≥12.

15. The method according to any one of claims 12 to 13, characterized in that: The decalcification treatment is carried out using carbon dioxide.

16. The method according to any one of claims 12 to 13, characterized in that: After the decalcification treatment and the pH adjustment, the pH value of the ammonium sulfate solution is 10-11.

17. The method according to any one of claims 12 to 13, characterized in that: The evaporative crystallization comprises: After the pH-adjusted ammonium sulfate solution is subjected to solid-liquid separation, an MVR crystallization system is used to evaporate and crystallize the solution obtained after the solid-liquid separation.

Citation Information

Patent Citations

  • Method for recycling negative electrode material of scrapped lithium ion battery

    CN117477082A

  • Treatment process and application of lithium hexafluorophosphate in waste batteries

    CN118724024A